Periprosthetic joint infection in orthopaedic surgical oncology - Zuidhof, Roel-Jan W. J.; Löwik, Claudia A. M.; Ploegmakers, Joris J. W.; Dijkstra, Sander P. D.; Wouthuyzen-Bakker, Marjan; Jutte, Paul C. (Annals of Joint, 2019)
The use of tumor megaprostheses in patients with bone tumors has provided a successful limb salvaging treatment option in oncology patients. Unfortunately, the prevalence of periprosthetic infection is much higher after oncologic joint arthroplasty than after regular joint arthroplasty, ranging from 7% to 28%. This increased risk of infection is caused by local and systemic immunodeficiency due to chemotherapy and radiotherapy, long duration of surgery, large wound areas and the use of large implants. This review focused on specific issues regarding infected megaprostheses in oncology patients, aiming to give directions for the prevention, diagnosis and treatment of infected megaprostheses.